Effects of cascade reporting of susceptibility profiles for Enterobacterales on broad-spectrum antibiotics use and resistance. Issue 2 (21st February 2022) - Heireman, Laura; Vandendriessche, Stien; Coorevits, Liselotte; Buyle, Franky; De Waele, Jan; Vogelaers, Dirk; Verhasselt, Bruno; Boelens, Jerina
Abstract : Objective: To reduce the inappropriate use of broad-spectrum antibiotics in a 1000+ bed acute tertiary care hospital by the introduction of cascade antimicrobial susceptibility reporting for Enterobacterales. Methods: Over a 1-year period, we selectively suppressed reporting of susceptibility to the broad-spectrum antibiotics piperacillin-tazobactam (TZP) and meropenem (MEM) for Enterobacterales strains susceptible to amoxicillin-clavulanic acid (AMC) and negative for extended-spectrum β-lactamase (ESBL). We measured the effects on hospital-wide antibiotic consumption (defined daily doses/1000 admissions) and resistance of Escherichia coli and Klebsiella pneumoniae on two levels. First, we compared resistance and antibiotic use for the antibiotics impacted by the intervention (AMC, TZP and MEM) with control antibiotics that were consistently reported (fluoroquinolones, trimethoprim-sulfamethoxazole and third-generation cephalosporins). Second, we compared the resistance for TZP and MEM with a control pathogen ( Pseudomonas aeruginosa ) and studied the impact on rate of Clostridioides difficile -associated diarrhoea in our hospital. Results: We observed an overall increased use of AMC relative to overall antibiotic consumption (20.0%, p<0.0001) together with a decreased use of TZP (−11.9%, p=0.049) and unchanged use of MEM (p=0.68) relative to overall antibiotic consumption. As for resistance, the number of ESBL-positive K. pneumoniae strains diminished by 5.9% (p<0.0001). When focusing on intensive care units, the carbapenemase-producing Enterobacterales (CPE) rate also decreased by 4.5% (p=0.0091). For E. coli, no significant difference in ESBL (p=0.33) and CPE (p=0.48) rates were observed. No significant difference in the rate of C. difficile infections was observed (p=0.40). Conclusions: Restricted susceptibility reporting of TZP and MEM was associated with a significant increased use of AMC and decreased use of TZP relative to overall antibiotic consumption and significant reduction in ESBL- and CPE-positive K. pneumoniae strains.